2021
DOI: 10.3390/nano11040950
|View full text |Cite
|
Sign up to set email alerts
|

Gold-seeded Lithium Niobate Nanoparticles: Influence of Gold Surface Coverage on Second Harmonic Properties

Abstract: Hybrid nanoparticles composed of an efficient nonlinear optical core and a gold shell can enhance and tune the nonlinear optical emission thanks to the plasmonic effect. However the influence of an incomplete gold shell, i.e., isolated gold nano-islands, is still not well studied. Here LiNbO3 (LN) core nanoparticles of 45 nm were coated with various densities of gold nano-seeds (AuSeeds). As both LN and AuSeeds bear negative surface charge, a positively-charged polymer was first coated onto LN. The number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…For a seeded‐growth mechanism, the ratio between the gold seeds and the precursor of Au species to be reduced is a factor influencing the homogeneous or inhomogeneous growth of Au NPs. [ 32 ] In a previous study, we found from inductive coupled plasma atomic emission spectroscopy (ICP‐AES) analysis that the maximum surface coverage of LN by AuSeeds at ≈30% is already attained for both AuSeeds:LN ratios (1000 and 3000) [ 24 ] whereas X‐ray photoelectron spectroscopy (XPS) data revealed different Au:Nb atomic ratios at 0.91 and 1.28, respectively (Table S1, Supporting Information). Effect of these two AuSeeds densities on the final LN@Au structures and properties is thus worth to be studied.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a seeded‐growth mechanism, the ratio between the gold seeds and the precursor of Au species to be reduced is a factor influencing the homogeneous or inhomogeneous growth of Au NPs. [ 32 ] In a previous study, we found from inductive coupled plasma atomic emission spectroscopy (ICP‐AES) analysis that the maximum surface coverage of LN by AuSeeds at ≈30% is already attained for both AuSeeds:LN ratios (1000 and 3000) [ 24 ] whereas X‐ray photoelectron spectroscopy (XPS) data revealed different Au:Nb atomic ratios at 0.91 and 1.28, respectively (Table S1, Supporting Information). Effect of these two AuSeeds densities on the final LN@Au structures and properties is thus worth to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, if free Au NPs are observed in LN@Au samples prepared from LN@BPEI@AuSeeds3000, previous TEM investigations revealed the absence of unattached AuSeeds for every AuSeeds:LN ratio studied after their attachment to LN@BPEI. [ 24 ] Upon addition of NH 2 OH, HCl to catalyze the reduction of Au 3+ to Au 0 , lack of space area between the closely packed Au NPs at the surface of the LN@BPEI@AuSeeds3000 might explain the release of weakly bonded AuSeeds from the LN surface and their subsequent growth to produce unbound Au NPs. Due to the lower surface density coverage before reduction, this latter scenario is less prone to occur for the LN@BPEI@AuSeeds1000 samples that finally result in a more homogeneous population of LN@Au NPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations